The Confluence of HIV-1 and HIV-2: Implications for Disease Progression and Insights for Therapy - Edwin Magomere; Charles Ochieng’ Olwal; Becky Ewurama Tetteh; Mark Appeaning; Thumbi Ndung’u; George Boateng Kyei; Peter Kojo Quashie (International Journal of Microbiology)
Two distinct types of human immunodeficiency virus (HIV), namely, HIV-1 and HIV-2 exist. HIV-1 is responsible for the global pandemic and has an aggressive pathogenesis. On the contrary, HIV-2 is not only less aggressive but also confined to West and Central African regions. Even after four decades of HIV research, a scalable cure or effective vaccine against HIV remains elusive. Consequently, the concept of a functional cure or vaccine, targeting to limit disease progression, allowing sufficient time for the immune response to clear the virus, has gained traction. Efforts to identify new therapeutic targets for development of a functional cure have focused on elite controllers, that is, individuals who naturally control HIV-1 infection in the absence of antiretroviral therapy. However, little progress has been associated with these efforts perhaps due to the scarcity of elite controllers, who make up only 0.15% of HIV-1 infected population globally. A distinct but largely unexplored subset of HIV patients comprise HIV-1 and HIV-2 dually infected individuals. This group of patients naturally presents with an attenuated disease progression phenotype akin to natural controllers. In this review, we discuss the attenuated disease progression phenomenon in dually infected individuals and offer potential explanations for this unanticipated observation. Additionally, we propose potential therapeutic and/or vaccine strategies that could leverage interactions of HIV-1 and HIV-2. Such strategies are likely to inform alternative therapeutics. A thorough understanding of the mechanism underlying the attenuated disease progression phenotype in HIV dually infected individuals is crucial for the design of a functional cure.